European public health reports between expectations and reality (Italian Journal of Public Health, 2004)
Despite the great variety of regional and national health reports that have been drawn up in the EuropeanRegion, authors and users demand that health reports should be conceived as an instrument for healthpolicy.Under the research project “Evaluation of national and regional health reports (Eva PHR)” within the HealthMonitoring Programme of the European Union, the policy impact of health reports drawn up in 19 Europeancountries has been analysed with the objective of identifying best practice models. Modelled on an agreedlist of criteria, regional and national health reports were analysed with regard to their contents, structureand political relevance. Simultaneously, a qualitative analysis of semi-structured interviews held with policymakers (politicians, decision-makers in administration and stakeholders) on the experiences, ideas andexpectations they have with regard to health reporting was carried out.The presently prevailing practice of descriptive health reporting is characterised by a great heterogeneityamong all received reports and by a discrepancy between the expectations of policy makers and actualhealth reporting. Whereas most health reports in Europe focus on covering the widest possible range ofissues and on presenting existing data and indicators accordingly, most decision makers attach considera-ble importance to linking epidemiology with information about health care provision, financing and evalua-tion of programmes and activities.To increase the policy relevance of public health reporting, authors should work in close collaboration withpolicy makers and consider different kinds of products with differing forms and content. Furthermore, thedevelopment of methodical instruments for routine policy oriented health reporting could close the currentgap between the perceptions of authors and users.
Keywords: Eva PHR; health reporting